How School Principals Sustain Success over Time
VIII, 244 p.
Keywords: This pioneering account of a longitudinal study – the International Successful School Principal Project (ISSPP) - of successful school principals over five years in Australia, Denmark, Norway, Sweden, England and the USA will be required reading for educationalists. It contains fresh insights that take our understanding of successful school to a new level. This book is a pioneering effort that offers a richer understanding of how leadership contributes to school success across different national contexts. The book provides a balanced, data-driven approach that seeks to identify thematic similarities even as it honours variations in leadership practices that are linked to specific societies. Philip Hallinger, Professor, Hong Kong Institute of Education This book moves the educational leadership field forward on three important fronts: it provides a rare, longitudinal, picture of leadership and change in a large number of schools; it unearths some of the key leader – related factors that explain a school’s ability to sustain improvements over long periods of time and; it constitutes one of the very few international, comparative, cross-cultural data sets available about school leadership. Kenneth Leithwood , Professor OISE, University of Toronto 'Standards and testing are a fact of life'. Or are they? It requires exceptional leaders to 'fly below the political radar'. It requires a strong grasp of moral purpose for leaders to reinterpret improvement and accountability. It requires courage and conviction to challenge conventional wisdom and to steer a course grounded in enduring educational principles. The great strength of this book is its international reach, powerfully illustrating how different cultural traditions and differing forms of leadership are responding to pervasive, and often insidious, global pressures. John MacBeath, Professor Emeritus, University of Cambridge Thechapters in this book provide much needed longitudinal accounts of leadership in schools and they do so by attending to similarities and differences across countries. Such cross national accounts offer great promise in generating new knowledge about school leadership and management. James P. Spillane, Professor, Northwestern University.